MANAJEMEN KEGIATAN EKSTRAKURIKULER DALAM PEMBENTUKAN KARAKTER DAN KEDISIPLINAN SISWA DI MADRASAH TSANAWIYAH ANWARUL HASANIYYAH TABALONG - Hasna ‘Afifah; Irpina Irpina; Nuril Anisa; Syahrani Syahrani (CV. ADIBA AISHA AMIRA, 2023)
Extracurricular activities are educational activities that can be carried out outside class hours, these activities are carried out inside or outside the school environment to expand knowledge, improve skills, and internalize values or rules. This research aims to describe extracurricular activities in building the character and discipline of students at MTs Anwarul Hasaniyyah Tabalong. Education is not only limited to transferring cognitive knowledge, but also an effort to form a society with character. Character education is efforts designed and implemented systematically to instill behavioral values in students. One way to implement character education in schools is by carrying out and developing students in extracurricular activities. Extracurricular activities are activities carried out by students outside class hours, these activities are a place to accommodate students' talents and interests outside of intracurricular activities. In extracurricular activities an individual tries to express his abilities, potential, talents and interests to achieve a level of personal development. This is instilled in students to create individuals who have good skills and personalities. The importance of extracurricular management is not only in individual development, but also in building an inclusive and supportive school culture. With effective management, extracurriculars can become a forum for developing creativity, collaboration and appreciation for diversity among students.